Indoor and Outdoor Air Fungus Bioaerosols in Khorramabad Day Care Child Centers Western of Iran, 2018 - Asghar Sepahvand; Katayan Salim; Edris Hoseinzadeh; Khadijeh Jafari; Rezvan Mohammadrezaei Khorramabadi (Journal of Environmental Health and Sustainable Development, 2020)
Introduction: the aim of this study was to determine the quantity and quality of indoor and outdoor air fungus bioaerosols in Khorramabad day care child centers. Materials and Methods: A total of 180 air samples were collected from 10 centers in 2018. The samples included 7 indoor and 2 outdoor sampling points. The total number of children was 580. Sampling of fungal bioaerosols was performed by the ZEFON pump (ZEFON factory, USA) with a flow rate of 28.3 L/min. The Sabouraud Dextrose Agar containing chloramphenicol was used as the culture medium. Relative humidity and temperature were measured by a Hygro-Thermometer (TES-1360A- Taiwan-made Humidity and temperature meter). Results: The results showed that 96.1 % of the samples were positive and had grown colonies. The highest amount of fungal agents in the indoor air and outdoor air were 175.58 CFU/m3 and 274.56 CFU/m3 in May, while the lowest rates were 3.4 CFU/m3 and 7.8 CFU/m3 in July, respectively. Aspergillus niger and Mucor were the most highly abundant fungus genera, while Fusarium was the lowest one. In all samples, the I/O (indoor/outdoor) ratio was more than 1; so, fungal bioaerosols in indoor environments were dominant than the outdoor fungal bioaerosols. The relationship of fungal bioaerosols with RH and T)°C( was significant (P-value = 0.001). Conclusion: Generally, the amount of contamination is considerable in the studied day care child centers. Therefore, ventilation modification is recommended by a purifier filter. Moreover, the ventilation conditions and favorable air standards should be monitored continuously by supervisory authorities.